2019
DOI: 10.20892/j.issn.2095-3941.2018.0306
|View full text |Cite
|
Sign up to set email alerts
|

LAG-3 expression on tumor-infiltrating T cells in soft tissue sarcoma correlates with poor survival

Abstract: Objective To elucidate the role and prognostic significance of lymphocyte activation-gene-3 (LAG-3) in soft tissue sarcoma (STS). Methods The expression of LAG-3 in patient and matched normal blood samples was analyzed by flow cytometry. The localization and prognostic values of LAG-3 + cells in 163 STS patients were analyzed by immunohistochemistry. In addition, the expression of tumor-infiltrating CD3 + T, CD4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…In some cases, LAG3 can be found in a soluble form (sLAG3) [ 44 ]. In a study carried out on 163 STS-affected patients, it was found that the frequency of CD8 + and CD4 + T lymphocytes expressing LAG3 is higher than in healthy controls; moreover, the expression is correlated with the presence of TILs CD8 + , with a severe prognosis and advanced tumor stage [ 45 ]. LAG3 is often co-expressed with PD1, and rarely with TIM3 [ 33 ].…”
Section: Molecular Markers Associated With Prognosismentioning
confidence: 99%
“…In some cases, LAG3 can be found in a soluble form (sLAG3) [ 44 ]. In a study carried out on 163 STS-affected patients, it was found that the frequency of CD8 + and CD4 + T lymphocytes expressing LAG3 is higher than in healthy controls; moreover, the expression is correlated with the presence of TILs CD8 + , with a severe prognosis and advanced tumor stage [ 45 ]. LAG3 is often co-expressed with PD1, and rarely with TIM3 [ 33 ].…”
Section: Molecular Markers Associated With Prognosismentioning
confidence: 99%
“…The expression and function of LAG-3 in the TME was investigated in glioblastoma by Harris-Bookman and co-workers [ 167 ], who demonstrated its expression mainly in TIL. Moreover, they setup an orthotopic preclinical model of glioblastoma and observed that combined therapy using anti-LAG-3 and anti-PD-1 antibodies was more effective in terms of increased overall survival than the single therapy.…”
Section: Ic As Immunotherapeutic Targets In Pediatric Solid Cancersmentioning
confidence: 99%
“…TIGIT is a cell surface protein identified by bioinformatics analysis of the genes expressed in activated T cells. TIGIT is composed of a single Ig domain, a type I trans-membrane domain and a single intracellular immune-receptor tyrosine-based in- The expression and function of LAG-3 in the TME was investigated in glioblastoma by Harris-Bookman and co-workers [167], who demonstrated its expression mainly in TIL. Moreover, they setup an orthotopic preclinical model of glioblastoma and observed that combined therapy using anti-LAG-3 and anti-PD-1 antibodies was more effective in terms of increased overall survival than the single therapy.…”
Section: Tigitmentioning
confidence: 99%
“…Specifically, the expression of LAG-3 on tumor infiltrating lymphocytes (17), natural killer cells (18), B cells (19) and dendritic cells (20) indicates its involvement in a widespread and complex immune pathways. LAG-3 is evaluated in various types of cancer (21)(22)(23) and has a synergistic effect with PD-1/PD-L1 axis (24)(25)(26). According to our recent study, high expression of LAG-3 in tumor tissue indicated an unfavorable prognosis in HCC (27).…”
Section: Introductionmentioning
confidence: 99%